Cardiorespiratory disease diagnosis in Holstein calves - Fraser, Brandon Camerson (Kansas State University, 2013)
Minimal research is available pertaining to the suspected acute cardiac injury of cattle experiencing the early signs of respiratory disease. One of the limitations of cardiac disease diagnosis in cattle is the lack of accurate measurement of cardiac disease. Blood biomoarkers such as cardiac troponin I could be used. Cardiac troponin I is a serum biomarker for cardiac injury in humans and many veterinary species. The goal of this thesis is to evaluate biophysical changes including cardiac injury that holstien calves experience during acute pneumonia. The first objective of this research was to evaluate a point of care cardiac troponin I assay for use in the bovine. Purified bovine cardiac troponin I was used to validate the accuracy of the assay over a wide range of concentrations in an in vitro experiment. This point of care assay was capable of accurately identifying bovine cardiac troponin I. An in vivo experiment was conducted to evaluate concentrations of cardiac troponin I in healthy Holstein calves. Concentrations evaluated with the point of care assay were similar to concentrations of a previously validated immunoassay. The second objective was to evaluate biophysical changes including serum biochemistry, complete blood count, cardiac troponin I, and high resolution digital thermography in Holstein calves during the first fourteen days after induction of pneumonia. Fibrinogen concentration increased with lung disease severity. The changes observed were considered clinically significant. Cardiac troponin I increased as pneumonia progressed during the study in this population.
Keywords: Heart; CardiacCattle; Cardiorespiratory; RespiratoryBovine; Veterinary Medicine (0778)